Pembelajaran Inkuiri Terbimbing Berbantuan Alat Peraga Konstanta Pegas Digital untuk Meningkatkan Keterampilan Generik Sains - Nur Khoiri; Choirul Huda; Hadhijah Assegaf (Physics Education Research Journal, 2020)
The research purpose is explored the effect of guided inquiry learning with digital spring for science generics skills. The subject of research are 70 student in XI MIPA SMAN 11 Semarang consisting of 35 students in the experimental group and 35 students in the control group. Design study uses Quasy Experiment Design, the type to be used is Nonequivalent Control Group Design. Data collection techniques through observation and questionnaire with a Likert scale. The results of data analysis from observation sheet on average experiment class = 3,22 and the average control class = 2,93. This study uses independent sample t-test show tcount ttable  that is  3,76 1,99 interpreted tcount ttable then Ho rejected Ho and accepted Ha. Based on the result of this research, it can be concluded that guided inquiry learning digital spring constant give positive influence to science generic skill student in SMAN 11 Semarang. Students' generic science skills were better after the implementation of guided inquiry learning assisted with teaching aids.